Optimal implementation of genomic selection in clone breeding programs exemplified in potato: II. Effect of selection strategy and cross‐selection method on long‐term genetic gain - Po‐Ya Wu; Benjamin Stich; Stefanie Hartje; Katja Muders; Vanessa Prigge; Delphine Van Inghelandt (The Plant Genome)
Abstract Different cross‐selection (CS) methods incorporating genomic selection (GS) have been used in diploid species to improve long‐term genetic gain and preserve diversity. However, their application to heterozygous and autotetraploid crops such as potato (Solanum tuberosum L.) is lacking so far. The objectives of our study were to (i) assess the effects of different CS methods and the incorporation of GS and genetic variability monitoring on both short‐ and long‐term genetic gains compared to strategies using phenotypic selection (PS); (ii) evaluate the changes in genetic variability and the efficiency of converting diversity into genetic gain across different CS methods; and (iii) investigate the interaction effects between different genetic architectures and CS methods on long‐term genetic gain. In our simulation results, implementing GS with optimal selected proportions had increased short‐ and long‐term genetic gain compared to any PS strategy. The CS method considering additive and dominance effects to predict progeny mean based on simulated progenies (MEGV‐O) achieved the highest long‐term genetic gain among the assessed mean‐based CS methods. Compared to MEGV‐O and usefulness criteria (UC), the linear combination of UC and genome‐wide diversity (called EUCD) maintained the same level of genetic gain but resulted in higher diversity and a lower number of fixed QTLs. Moreover, EUCD had a relatively high degree of efficiency in converting diversity into genetic gain. However, choosing the most appropriate weight to account for diversity in EUCD depends on the genetic architecture of the target trait and the breeder's objectives. Our results provide breeders with concrete methods to improve their potato breeding programs.